A miR-327–FGF10–FGFR2-mediated autocrine signaling mechanism controls white fat browning - Carina Fischer (Nature Portfolio, 2017)
White adipocytes can be stimulated to express thermogenic genes in a process known as beiging. Here, the authors show that miR-327 is downregulated during beiging, which releases FGF10 from inhibition and supports beige adipocyte formation via signaling through FGFR2.